PENINGKATAN AKTIVITAS BELAJAR TEMATIK MELALUI MODEL DISCOVERY LEARNING (PTK pada Kelas III B SDN 09 Kota Bengkulu) - Apriyanti, Puspita; Arifin, Muhammad (TRIADIK, 2017)
AbstractThis study aims to improve student learning activities in thematic learning through discovery learning models. The type of research used is classroom action research. The subjects of this study were the third grade students of SD Negeri 09 Kota Bengkulu in the second semester of the 2017/2018 school year, totaling 31 students. Data collection tools in the form of observation sheets of teacher activities and student activities. The analysis technique uses qualitative descriptive analysis. The results of the study in the first cycle the percentage of student activity asked 22.6%, elite activities carried out in two cycles. Each cycle consists of planning, the implementation of students expressing opinions reached 38.7%, activities in timeliness collected tasks 6.5%. In the second cycle, asking activities increased to 41.9%, expressing opinions 61.3%, activities collecting tasks on time 90.3%. This shows that the discovery learning model can increase the activity of students in thematic learning class III B SD 09 Kota BengkuluKeywords: activity, thematic, discovery learning